The characteristics of the potentiodynamic potential/current profiles obtained with the Ni/0.5N H2SO4 interface. A contribution to the mechanism of the electrode process - Real, Silvia Graciela (1980)
Electrochemical data derived from different simple and complex potentiodynamic techniques for the Ni/0.5 N H2SO4 interface furnish a new insight about the activation and initial stage passivation of nickel. The anodic dissolution of nickel involves a metal surface which is either partially or completely covered by species such as NiOH, [NiOH.Ni(OH)2] or [Ni(OH)2.NiOOH]. The chemical dissolution of the various species in the acid electrolyte occurs at different rates. The relative dissolution rates can be estimated from the data derived from the complex triangular potential perturbations. The change of the E/I profile during cycling is explained through a complex reaction sequence which is in agreement with recently postulated reaction schemes and reported optical data.